On the sensitivity of HCPWR microcell calculations to geometrical treatment - Sbaffoni, María Mónica; Abbate, Máximo Julio; Patiño, Néstor Edmundo (Comisión Nacional de Energía Atómica; Argentina)
Fil: Sbaffoni, María Mónica Comisión Nacional de Energía Atómica; Argentina